2021
DOI: 10.1016/j.ijid.2021.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of viral hepatitis C genotypes 1 and 2 by sofosbuvir and ledipasvir with or without ribavirin combination: A possible alternative to pangenotypic treatment in a low-income country?

Abstract: Please cite this article as: { doi: https://doi.org/ This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Compounds containing spirocyclopropane structural units exist in many synthetic and natural compounds, and many spirocyclopropanes have antitumor and antiviral activities. For example, ledipasvir is a drug used to treat hepatitis C. 10 In 2000, the Elinson group reported that the electrochemical Wideqvist reaction of malononitrile (1) and carbonyl compounds 2 using sodium bromide as the electro-lyte and ethanol as the solvent gave tetracyanocyclopropanes 3 (Scheme 1). 11 When the carbonyl compound was cyclohexanone (2a), the final product was the pyrroline spirocyclic compound 4.…”
Section: Electrochemically Mediated Synthesis Of Spirocyclopropanesmentioning
confidence: 99%
“…Compounds containing spirocyclopropane structural units exist in many synthetic and natural compounds, and many spirocyclopropanes have antitumor and antiviral activities. For example, ledipasvir is a drug used to treat hepatitis C. 10 In 2000, the Elinson group reported that the electrochemical Wideqvist reaction of malononitrile (1) and carbonyl compounds 2 using sodium bromide as the electro-lyte and ethanol as the solvent gave tetracyanocyclopropanes 3 (Scheme 1). 11 When the carbonyl compound was cyclohexanone (2a), the final product was the pyrroline spirocyclic compound 4.…”
Section: Electrochemically Mediated Synthesis Of Spirocyclopropanesmentioning
confidence: 99%